Analisis Perencanaan, Pelaksanaan dan Penilaian Kegiatan Ekstrakurikuler di SD Laboratorium UPI Cibiru dan SD Percobaan - Geovany Sabaritha Nimaisa; Nurva Miliano; Sekar Ayu Cahyani; Agus Mulyana (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2024)
Extracurricular activities are an important program for schools to organize as a forum for developing students' potential and interests. Therefore, this research was conducted to find out and examine extracurricular activities at the UPI Cibiru Laboratory Elementary School and SD Percobaan starting from the stages of planning, implementation and assessment.This research was conducted with a qualitative approach with descriptive analysis techniques. The main data collection was carried out using observation and interview techniques and secondary data collection was carried out using literature techniques from various sources, especially journals. The results of this study indicate that in the planning stage, trainers and guest teachers will design a program for one semester that contains targets, stages of learning and evaluation. After a clear program design, students were given the opportunity to choose an extracurricular activity of their choice that they would participate in for one semester apart from the compulsory extracurricular activities in the two schools. At the implementation stage, both schools have implemented each extracurricular activity by adjusting the learning schedule. Extracurricular activities in both schools have also been able to make various achievements, but still the main focus of the implementation of extracurricular activities is to facilitate students in developing their interests and potential. Finally, at the assessment stage, coaches and guest teachers carry out skills tests, the results of which will then be processed and adjusted to the assessment format according to their respective school policies and distributed to students in the form of report cards.